Synthesis and Characterization of N,N,O-Tridentate Aminophenolate Zinc Complexes and Their Catalysis in the Ring-Opening Polymerization of Lactides - Lu, Wei-Yi; Wu, Kuo-Hui; Chen, Hsuan-Ying; Lin, Chu-Chieh (Frontiers in Chemistry, 2019)
A series of aminophenolate ligands with various pendant groups and associated ethyl Zn complexes were synthesized and studied as catalysts for the ring-opening polymerization (ROP) of lactides (LAs). The thiophenylmethyl group (L4ZnEt) increased the catalytic activity more than benzyl group (L1ZnEt) did, and 2-fluorobenzyl (L3ZnEt) and 2-methoxybenzyl (L2ZnEt) groups had the opposite effect. In addition, the LA polymerization mechanism proved by Nuclear Magnetic Resonance and Density Function Theory was that LA was attracted by H···O bond of an α-hydrogen of the LA molecule and the phenoxyl oxygen of the catalyst. After the dissociation of amino group from the Al atom, the benzyl alcohol initiated LA without replacing ethyl group of Zn complex. It is the first case that ethyl group is regarded as a ligand and cannot be replaced by benzyl alcohol, and this information is very important for the mechanism study of ROP.